Special School vs Mainstream School: Parents’ Perspective on School Choice for Students with Disabilities - Sujarwanto, Sujarwanto; Ashar, Muhammad Nurul; Purwoko, Budi; Ardianingsih, Febrita (Department of Special Education, 2023)
This study aimed to discover the experience of choosing a school among parents of children with disabilities in Indonesia and found out their opinion about the current school placement of their children. This study applied the quantitative -survey study Data were collected using a questionnaire. Parents from one mainstream school and one special school in Indonesia completed the questionnaire. Results from the questionnaire were analyzed manually. This study revealed that parents from the mainstream school were influenced by mixed factors, compared to parents from the special school, which mainly based on the instrumental-academic perspective. Regarding key persons, parents in the mainstream and special school were majorly making their own decision or supported by family. It is also found that parents were satisfied with the current school placement, even though the process of choosing school is not easy. Some suggestions for practice and further study are also discussed.